A thematic content analysis of #cheatmeal images on social media: Characterizing an emerging dietary trend. Issue 6 (11th January 2017) - Pila, Eva; Mond, Jonathan M.; Griffiths, Scott; Mitchison, Deborah; Murray, Stuart B.
Abstract: Despite the pervasive social endorsement of "cheat meals" within pro‐muscularity online communities, there is an absence of empirical work examining this dietary phenomenon. The present study aimed to characterize cheat meals, and explore the meaning ascribed to engagement in this practice. Thematic content analysis was employed to code the photographic and textual elements of a sample ( n = 600) that was extracted from over 1.6 million images marked with the #cheatmeal tag on the social networking site, Instagram. Analysis of the volume and type of food revealed the presence of very large quantities (54.5%) of calorie‐dense foods (71.3%) that was rated to qualify as an objective binge episode. Photographic content of people commonly portrayed highly‐muscular bodies (60.7%) in the act of intentional body exposure (40.0%). Meanwhile, textual content exemplified the idealization of overconsumption, a strict commitment to fitness, and a reward‐based framework around diet and fitness. Collectively, these findings position cheat meals as goal‐oriented dietary practices in the pursuit of physique‐ideals, thus underscoring the potential clinical repercussions of this socially‐endorsed dietary phenomenon.